Гончарний промисел жителів села Микільська Слобідка у середині ХІХ ст. (за матеріалами новітніх археологічних досліджень) - Оленич, А.М.; Оленич, А.М. (Археологія і давня історія України, 2018)
Статтю присвячено введенню до наукового обігу матеріалів археологічних досліджень на території села Микільська Слобідка, що свідчать про існування в ньому гончарного осередку модерного часу. Охарактеризовано основний асортимент продукції та особливості гончарної сировини. The paper introduces materials from the archaeological excavations on the territory of the village of the 16th—19th centuries Mykilska Slobidka. The village has not been subject to systemic archaeological excavations before. In 2016—2018 we carried out the investigating in different parts of the village. It was fixed that despite the modern urban development, the cultural layer was preserved in some parts of the village. Obtaining materials indicate the existence of pottery production there. The most interesting is the ceramic collection associated with the pottery complex of the beginning of the 19th century. The collection allows us to characterize the assortment of the pottery manufacturing in the Mykilska Slobidka village in the first half of the 19th century. Among the typical products of the workshops were pots decorated with white and red engobe painting, jugs, bowls, lids, mugs, flowerpots, bricks and probably tiles etc. It is interesting that there are no pottery clay deposits in the vicinity of the village. So it is possibly the clay was brought from other villages, may be on the other (right) bank of the Dnieper River.